PENGARUH MOTIVASI KERJA DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN - Parmin, Yohanes (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This study aims to determine the influence of work motivation and teamwork on employee performance. The research method used was quantitative, with a saturated sampling approach, where the entire population was used as a sample of 45 employees. As for the results of the study, it can be explained that the influence of work motivation on employee performance produces a t count of 6.941 greater than the t table of 1.668 (6.941>1.668) so that Ho is rejected and Ha is accepted with a significance level of 0.000 <0.05. Thus, it can be concluded that there is a significant influence between Work Motivation (X1) on employee performance partially. Likewise, the influence of Teamwork (X2) on Employee Performance (Y) can be explained that the t count result of 7.214 is greater than the t table of 1.668 (7.214>1.668) so that Ho is rejected and Ha is accepted with a significance level of 0.000 <0.05. Thus, it can be concluded that there is a significant influence between Team Performance on Employee Performance partially. The influence of Work Motivation (X1) and Teamwork (X2) on Employee Performance (Y) simultaneously can be explained that the calculated F result of 43.123 is greater than the Ftable of 3.14 (43.123>3.14) so that Ho is rejected and Ha is accepted with a significance level of 0.000 <0.05. Based on these results, it can be concluded that simultaneously there is a significant influence between motivation and teamwork on employee performance.